2007
DOI: 10.2353/ajpath.2007.070056
|View full text |Cite
|
Sign up to set email alerts
|

A Thrombospondin-1 Antagonist of Transforming Growth Factor-β Activation Blocks Cardiomyopathy in Rats with Diabetes and Elevated Angiotensin II

Abstract: In diabetes and hypertension, the induction of increased transforming growth factor-␤ (TGF-␤) activity due to glucose and angiotensin II is a significant factor in the development of fibrosis and organ failure. We showed previously that glucose and angiotensin II induce the latent TGF-␤ activator thrombospondin-1 (TSP1). Because activation of latent TGF-␤ is a major means of regulating TGF-␤, we addressed the role of TSP1-mediated TGF-␤ activation in the development of diabetic cardiomyopathy exacerbated by ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
91
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 77 publications
6
91
0
Order By: Relevance
“…Moreover, LSKL treatment did not have any demonstrable effects on tissue homeostasis in wild-type C57BL/6J (data not shown), similar to our observations in normal rats receiving long-term LSKL peptide treatment. 39 In conclusion, these studies establish that blockade of TSP1-mediated TGF-␤ activation is an effective therapeutic target for treatment of the renal complications of diabetes. These studies suggest that blockade of TSP1-mediated TGF-␤ activation is a selective approach to controlling excessive TGF-␤ levels in diabetes and lacks the adverse effects associated with global inhibition of TGF-␤ signaling.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Moreover, LSKL treatment did not have any demonstrable effects on tissue homeostasis in wild-type C57BL/6J (data not shown), similar to our observations in normal rats receiving long-term LSKL peptide treatment. 39 In conclusion, these studies establish that blockade of TSP1-mediated TGF-␤ activation is an effective therapeutic target for treatment of the renal complications of diabetes. These studies suggest that blockade of TSP1-mediated TGF-␤ activation is a selective approach to controlling excessive TGF-␤ levels in diabetes and lacks the adverse effects associated with global inhibition of TGF-␤ signaling.…”
Section: Discussionmentioning
confidence: 68%
“…7,30,35,36,38,39,53,54 In the present studies, we addressed whether selective targeting of only TGF-␤ activated by TSP1 would be an effective approach to reduce renal dysfunction in a mouse model of type 1 diabetes. These studies showed that i.p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] TSP-1 blockade has been shown to reduce TGF-␤1 signaling and tissue fibrosis. [25][26][27][28] TSP-1 expression also markedly increased after experimental acute pancreatitis. 22 Thus, it would be expected that PEDF and TSP-1 would be reciprocally regulated if PEDF functions to inhibit fibrosis in the pancreas.…”
mentioning
confidence: 90%
“…TSP-1 promotes the events associated with diabetic nephropathy: mesangial cell proliferation and increased matrix production by mesangial cells (21)(22)(23)(24). A peptide blocking the activation of transforming growth factor-␤ activation by TSP-1 prevented progression of cardiac fibrosis and improved cardiac function in a rat model, implicating TSP-1 in development of diabetic cardiomyopathy (25). Recently, we reported increased levels of TSP-1 in macrovessels of diabetic Zucker rats (26).…”
mentioning
confidence: 98%